Table of Content - - (Journal of Islamic Sciences, 2023)
Table of Content 1. Apocryphal writings relating to the Old and New Testaments and the Jewish and Christian position on it Mrs. Maha Abdel-Rahman Rahma Al-Shabrami 2. The penalty purposes in the Islamic Shariah Mr. Basil Ahmad dudeen 3. Practical issues in prayer during the Corona pandemic Mr. Abdelghaffar Saleh Harbi 4. The reality of Imam Al-Mahdi in the light of Islamic Shariah Prof. Dil Aqa WAQAR, Prof. Shirzad Azizi 5. The concept of monotheism (Tawhid) in the Jewish doctrines Lecturer Shorouq Mohammed Al-Tashlan 6. Imam Ghazali’s rational approaches in his book Al-Mustasfa – An empirical and analytical study – Dr. Nayef Abdul Rahman Al-Jabr, Mrs. Hind Saad Al-Harbi 7. The Impact of Contemporary Issues Jurisprudence (Fiqh al-Nawazil) on Islamic Feminism Dr. Fatima Juma Alwhash